2021
DOI: 10.1093/ehjacc/zuab015
|View full text |Cite
|
Sign up to set email alerts
|

Joint EAPCI/ACVC expert consensus document on percutaneous ventricular assist devices

Abstract: There has been a significant increase in the use of short-term percutaneous ventricular assist devices (pVADs) as acute circulatory support in cardiogenic shock and to provide haemodynamic support during interventional procedures, including high-risk percutaneous coronary interventions. Although frequently considered together, pVADs differ in their haemodynamic effects, management, indications, insertion techniques, and monitoring requirements. This consensus document summarizes the views of an expert panel by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 118 publications
0
60
0
1
Order By: Relevance
“…Management must respect all the principles of critical care, including care bundles and multidisciplinary team (MDT) practice, while aiming to resolve CS and avoiding complications. [4][5][6] At the point of referral or when CS is recognized, an emergency shock MDT should be convened to define the treatment pathway within the chain of survival in CS (Figure 1). 7 This includes rapidly determining and executing the critical care and MCS strategy and/or transferring to a CS center for ongoing management.…”
Section: General Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Management must respect all the principles of critical care, including care bundles and multidisciplinary team (MDT) practice, while aiming to resolve CS and avoiding complications. [4][5][6] At the point of referral or when CS is recognized, an emergency shock MDT should be convened to define the treatment pathway within the chain of survival in CS (Figure 1). 7 This includes rapidly determining and executing the critical care and MCS strategy and/or transferring to a CS center for ongoing management.…”
Section: General Principlesmentioning
confidence: 99%
“…[3][4][5][8][9][10] Studies have demonstrated that a standardized team-based approach in highvolume centers, using care protocols with early MCS coupled with close monitoring (invasive hemodynamics, biomarkers and echocardiography) has the potential to improve outcomes. [3][4][5][6][7][8][9][10]…”
Section: Acute Mechanical Circulatory Supportmentioning
confidence: 99%
“…Data from clinical studies evaluating use of ECMO in the setting of OHCA are limited and they report low survival rates and disappointing neurologic outcomes [36,37]. However, ECMO is still useful in situations requiring high flow support and optimal oxygenation [15,38]. Schmidt et al suggested 10 situations in which use of ECMO is often futile and included a case series of critically ill patients with long low-flow periods, lasting more than 30 min and more [39].…”
Section: Effectiveness Of Prompt Cardiac Assistancementioning
confidence: 99%
“…Given the heterogeneity of clinical presentations, the diversity of therapeutic approaches in the absence of large-scale randomized studies with unequivocal results, the United States and European recommendations remain poorly directive and precise concerning the type and the timing of MCS (level of recommendation IIBC for European Society of Cardiology; and IIAb for American, Indian, and Canadian Heart Failure and Interventional Cardiology societies) (7,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In 15–20% of the cases designated as refractory CS, classical drugs are ineffective. In these cases, mechanical circulatory supports (MCS) have been developed for a dual role: first, to ensure CO to prevent or treat organ failure secondary to hypoperfusion and second, to allow the unloading of the ventricles and to promote myocardial recovery ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%